Logistics Ecosystem Turbulence and Digital Logistics Agility: Evidence from Indonesian Third-Party Logistics Firms - Sumarna, Dani Leonidas; Vanessa Gaffar; Lili Adi Wibowo; H.Mokh. Adib Sultan (Riviera Publishing, 2026)
The logistics industry is increasingly operating within highly dynamic and uncertain environments driven by regulatory changes, rapid technological developments, market volatility, and global supply chain disruptions. These conditions have transformed logistics ecosystems into complex networks, particularly for third-party logistics (3PL) firms that must develop adaptive capabilities to remain competitive. This study examines the effect of Logistics Ecosystem Turbulence (LET) on Digital Logistics Agility (DLA) among third-party logistics (3PL) firms in West Java, Indonesia. Using a quantitative approach, this study applies partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4. The results indicate that LET has a positive and highly significant effect on DLA (? = 0.847, p < 0.001), with strong explanatory power (R² = 0.717; f² = 2.533). These findings demonstrate that environmental turbulence acts as a critical driver of digital logistics agility. The study contributes to the logistics and digital transformation literature by positioning ecosystem turbulence as a foundational antecedent of digital agility in emerging economies.